2018
DOI: 10.1136/bmjopen-2018-023152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social determinants of health on patients with advanced lung cancer: a prospective cohort study

Abstract: IntroductionSocioeconomic factors with an influence on human health are known as social determinants of health (SDH). There are some SDH studies in patients with lung cancer, but important exposures such as social isolation and loneliness have not been adequately investigated. This study will assess the influence of SDH, particularly social isolation and loneliness, on patients with advanced lung cancer in Japan.Methods and analysisThe inclusion criteria for this prospective cohort study will be as follows: a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Social support has been found to be a protective factor for the prevention and maintenance of many diseases (25). Previous studies reported that being married is a predictor of receiving standard care and better outcomes (26)(27)(28), while experiencing social isolation or loneliness has a negative influence on lung cancer patients (29). In our study, being married showed a similar protective effect for receiving timely surgery in both white and black patients, while the insignificance of the OR among black patients may be due to the smaller sample size of black patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been found to be a protective factor for the prevention and maintenance of many diseases (25). Previous studies reported that being married is a predictor of receiving standard care and better outcomes (26)(27)(28), while experiencing social isolation or loneliness has a negative influence on lung cancer patients (29). In our study, being married showed a similar protective effect for receiving timely surgery in both white and black patients, while the insignificance of the OR among black patients may be due to the smaller sample size of black patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The study was performed at a Japanese tertiary referral hospital (Hyogo Prefectural Amagasaki General Medical Center) between April 2018 and March 2020. The study protocol has previously been published (11) and was approved by the Hyogo Prefectural Amagasaki General Medical Center (# 29-164). The study was conducted in accordance with the Declaration of Helsinki (as revised in 2013).…”
Section: Study Design and Settingmentioning
confidence: 99%
“…] (timely surgery), [3] (algorithm for physician networks), [11] (adherence), [25] (adherence), [28] (treatment patterns), [59] (screening), [63] (screening; review), [ ] (virality of info), [34], [36] (knowledge), [37], [56] (social media messages), [57] (social media accuracy), [71] (academic productivity), [72] (academic collaboration) All studies using dyadic data (measured ties between any two entities) are marked with an underline. Social support 43% [4,5], [6] (youth; review), [8,9], [10 && ] (network index), [11], [15] (review), [16,18,19,22,24,25], [31 && ] (review), [32,33,40,41], [42] (partners), [44,45,[49][50][51][52][53]61,64,66,68], [69] (review),…”
Section: Outcomes Evaluatedmentioning
confidence: 99%
“…are used when a characteristic is suggested by not clearly stated in a manuscript. ], [15] (review), [16,18,19,24], [26] (social media), [30], [31 && ] (review), [35] (social integration), [36,45], [46] (needs returning to work), [48], [50] (changing relationships), [51] (needs for informal support), [52] (roles), [53] (perceived), [58] (information seeking; review), [60] (isolation), [62] (perceived support, alienation), [62], [63] (review), [68] (social roles, social support), [69] (social support; review), [74] Quality of life 14% [5,8], [14] (social/family wellbeing), [22,25], [33] (life satisfaction), [36,41,42], [48] (social/family wellbeing), [49,51,68,73] Mental health 19% [8] (distress), [10 && ], [11] (depression, alcohol), [32] (depression), [33] (depression, anxiety), [34] (distress, burden),…”
Section: Outcomes Evaluatedmentioning
confidence: 99%
See 1 more Smart Citation